Digital materials - evaluation of the possibilities of using selected hyperelastic models to describe constitutive relations - Mańkowski, Jarosław; Lipnicki, Jakub (Zielona Góra: Uniwersytet Zielonogórski)
The authors tried to identify the parameters of numerical models of digital materials, which are a kind of composite resulting from the manufacture of the product in 3D printers. With the arrangement of several heads of the printer, the new material can result from mixing of materials with radically different properties, during the process of producing single layer of the product.
Keywords: digital materials; hyperelastic; identification of models; FEM; 3D printing; PolyJet Matrix technology